Launching and Maintaining an Elementary Science Program in a Large City System. - Enwalws, Paul G. (Science Education, 1932)
The article presents information on the launch of an elementary science program in the public schools of Chicago, Illinois, in the year 1928. There were no specific courses of study organized for any particular subjects at that point of time. The theory was based upon the assumption that each teacher would develop initiative which would result in an improvement in his teaching that in turn would reflect in the quality of work done by his students. Chicago has been gradually tuning its school system from an eight-year elementary school, four-year senior-high school system, into the 6-3-3 plan of organization involving the use of the elementary school, junior-high school and senior-high school. Also, there are some schools in Chicago which have not got success in establishing a satisfactory program of elementary science.